Acute vascular response to cediranib treatment in human non-small-cell lung cancer xenografts with different tumour stromal architecture. Issue 2 (November 2015) - Jiang, Yanyan; Allen, Danny; Kersemans, Veerle; Devery, Aoife M.; Bokobza, Sivan M.; Smart, Sean; Ryan, Anderson J.
Highlights: We studied cediranib, a VEGFR tyrosine kinase inhibitor in lung cancer xenografts. Gadolinium-enhanced DCE-MRI was used to study acute vascular responses. Acute vascular response was associated with tumour stromal architecture. Tumour growth inhibition by cediranib was linked to acute vascular response. Acute vascular changes are a potential predictive marker of response to cediranib. Abstract: Objectives: Tumours can be categorised based on their stromal architecture into tumour vessel and stromal vessel phenotypes, and the phenotypes have been suggested to define tumour response to chronic treatment with a VEGFR2 antibody. However, it is unclear whether the vascular phenotypes of tumours associate with acute vascular response to VEGFR tyrosine kinase inhibitors (TKI), or whether the early changes in vascular function are associated with subsequent changes in tumour size. This study was sought to address these questions by using xenograft models of human non-small cell lung cancer (NSCLC) representing stromal vessel phenotype (Calu-3) and tumour vessel phenotype (Calu-6), respectively. Methods: For dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI), nude mice bearing established Calu-3 or Calu-6 xenografts were treated with a potent pan-VEGFR TKI, cediranib (6 mg/kg), at 0 h and 22 h. DCE-MRI was performed 2 h before the first dose and 2 h after the second dose of cediranib to examine acute changes in tumour vessel perfusion. Tumours were harvested for hypoxia detection by CA9 immunohistochemistry. For tumour growth study, mice carrying established Calu-3 or Calu-6 tumours were treated with cediranib once daily for 5 days. Results: Twenty-four hours after cediranib administration, the perfusion of Calu-3 tumours was markedly reduced, with a significant increase in hypoxia. In contrast, neither perfusion nor hypoxia was significantly affected in Calu-6 tumours. Tumour regressions were induced in Calu-3 xenografts, but not in Calu-6 xenografts, although there was a trend towards tumour growth inhibition after 5 days of cediranib treatment. Conclusion: These findings suggest that tumour stromal architecture may associate with acute tumour vascular response to VEGFR TKI, and this acute tumour vascular response may be a promising early predictive marker of response to VEGFR TKI in NSCLC.